PENGEMBANGAN MODEL PEMBELAJARAN MEMBACA BERBASIS STORYTELLING INTERAKTIF TERINTEGRASI AI DAN GAMIFIKASI UNTUK MENINGKATKAN LITERASI SISWA SD - Silvia Meirisa; Andam Yulianti (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to develop a reading learning model based on interactive storytelling integrated with AI and gamification to improve elementary school students’ reading literacy. The research background stems from the low reading literacy performance of Indonesian students as reported by PISA 2022 and the dominance of conventional teaching methods with limited innovation. The research method applied was R&D using the 4D model (Define, Design, Develop, Disseminate). The subjects consisted of 80 elementary school students in Kerinci Regency, comprising 40 lower-grade students and 40 upper-grade students. Research instruments included reading literacy tests, motivation questionnaires, and student engagement observation sheets. The results indicated that the developed model was valid, with expert validation scores averaging 92% (content), 90% (media), and 88% (language). In terms of practicality, teacher responses (86%) and student responses (89%) confirmed that the model was easy to implement. Effectiveness testing revealed a significant improvement in literacy scores from a pre-test average of 63 to a post-test average of 82, with a gain score of 0.61 (moderate to high category). The integration of AI provided adaptive feedback tailored to students’ abilities, while gamification enhanced students’ motivation and active engagement in reading activities. Therefore, this model offers an innovative alternative to strengthen elementary students’ reading literacy in the digital era and Society 5.0.